Ultimate load behaviour of castellated beams with stiffened octagonal opening - Lim, S.Y. H.; Yatim, M. Y. M. (Penerbit Universiti Kebangsaan Malaysia, 2023)
Octagonal castellated beam is fabricated by adding spacer plates between the web joints of the hexagonal castellated beam to further increase the beam depth. The resulted deep beam is advantageous to enhance the shear carrying capacity and moment resistance. However, large web openings are prone to Vierendeel mechanism in the deformation that lowers the overall beam performance due to formation of plastic hinges. The present paper is concerned with non-linear analysis to predict the ultimate load behaviour of octagonal castellated beams. Finite element models were developed by using a commercial programme LUSAS. The numerical models were first validated against the experimental results reported by other researchers. This study aims to propose the ideal configuration of web opening stiffeners and evaluate the effectiveness of the additional stiffening material for different beam span lengths. Provision of ring stiffeners is effective in short span beams in respect of resistance to Vierendeel failure. The stiffeners have increased the ultimate load to the extent of 73% in which the strength restoration is considerably near to the capacity of its parent universal beam. In long span beams, however, the stiffeners can only improve the performance up to 26.61% with larger additional steel material than that of shorter span. In all cases, the stiffener thickness is found to be the governing factor to restoring the loss of shear strength due to large web openings. The number of stiffeners contributes no appreciable variation of ultimate load particularly in long span beams where bending is prominent.